Comparative susceptibilities and immune-related gene expressions of brown trout strains and their hybrids infected with Lactococcus garvieae and Yersinia ruckeri. Issue 91 (August 2019) - Ozturk, Rafet C.; Altinok, Ilhan; Turgut, Secil; Capkin, Erol
Abstract: Brown trout are polymorphic salmonid species, and it is of importance to investigate whether hybridization affects disease resistance. In this study, susceptibility of brown trout ( Salmo trutta Abant, Anatolian, Black Sea, and Caspius) strains and their hybrids to Lactococcus garvieae and Yersinia ruckeri as well as their immune-related gene expression profiles were studied. Results indicated that reciprocal hybridization did not affect disease resistance in brown trout strains. Purebred Black Sea strain of brown trout was the most resistant group against Y. ruckeri, followed by other Black Sea strain hybrids. On the other hand, purebred Anatolian strain was the most resistant group to L. garvieae, followed by other Anatolian strain hybrids. Expression pattern of target genes differed in families, but the overall gene expression was comparatively high in Y. ruckeri infected families. Upregulations were mainly significant at 7 and 28 d post infection while marginal regulations were observed 8 h after infection. Disease resistance status of strains was supported by high expression of immune-related genes such as major histocompatibility complex class I ( MHC-I ), immunoglobulin light chain ( IgL ), and antioxidant- and hemoglobin-related gene expression. Therefore, our findings suggest that Black Sea and Anatolian strains could be used to develop fish stock that are resistant for yersiniosis and lactocaccosis, respectively. Highlights: Reciprocal hybridization did not affect disease resistance in brown trout. Pure bred Black Sea strain is the most resistant group to Yersinia ruckeri . Purebred Anatolian strain is the most resistant group to Lactococcus garvieae. Disease resistance is supported by immune related genes expression such as MHC and IgL .